Factors determining self-harm - Shakya, YL; Acharya, R; Gupta, MP; Banjara, MR; Prasad, PR (Journal of Institute of Medicine Nepal, 2011)
Introduction: Self-harm forms a significant proportion of patient attending in emergency departments, typically 10-30 per 100000 people commit suicide annually. The objective of this study was to find out the factors responsible for self harm. Methods: This is a cross sectional study of 100 patients of self harm coming to Emergency Department of Tribhuvan University Teaching Hospital from 1stOctober 2007 to 31stMarch, 2008. Questionnaire about demographic information of patient along with details about cause of self harm, and any other illnesses associated was filled. Information about duration of arrival in emergency department, place of self harm was gathered. Patients were clinically examined and hematological and biochemical tests including liver function test and the type of poison used and its level in blood were examined. Results: Total number of patients with self harm was 100 (female - 71%; male- 29%).Among female, 16-30 years age group to be the largest (76%). Mean duration of arrival in emergency department was 3.08 hour. Metacid ingestion (29%) was found to be the most common cause for self harm. There is no difference of self harm for suicide and threat cause. Only 5% of patient with self harm has psychiatry illness in the past. Conclusions: Self harm forms a significant proportion of patient attending the Emergency department and the most common form of self harm used was metacid ingestion. There is compelling evidence for the need to improve delivery of care for patients who inflict self harm. Key words: Cause; emergency department; self harm. DOI: http://dx.doi.org/10.3126/joim.v32i3.4954 Journal of Institute of Medicine, December, 2010; 32:3 14-17